Clinical placements of medical students during a rapid scale-up of health professional education: a qualitative study - Jelle Stekelenburg; Daniel Dejene; Marco Versluis; Firew Ayalew; Tegbar Yigzaw; Nurilign Abebe Moges; Samuel Mengistu; Zewdie Aderaw (BMJ Open)
Objectives In response to a critical shortage of skilled workforce, Ethiopia has scaled up its health professional education (HPE) by increasing the number of training institutions and student enrolment capacity. However, strong evidence that shows how the HPE scale-up affected clinical placements is lacking. This study investigated the challenges and effects of the rapid HPE scale-up in clinical placements, and the adjustments made in response to the challenges.Design A qualitative study using focus group discussions and constructivist grounded theory was conducted in July–August 2022.Setting The teaching hospitals of six medical schools in Ethiopia.Participants 53 purposefully selected participants (25 clinician-teachers and 28 intern students).Measures Adequacy of skilled clinicians, student preparedness and learning environment were input measures. Quality of supervision, assessment, feedback and practice exposure are process measures. Clinical competence was an outcome measure.Results We identified six themes: (1) class size and student motivation, (2) availability of skilled and motivated clinician-teachers, (3) learning environment and practice management, (4) clinical supervision and assessment, (5) extent of exposure, and (6) clinical competence. The HPE upscaling caused student overcrowding, resource shortages and unconducive learning environments. Concerns were reported on clinical supervision, assessment, feedback, role modelling and programme management. Clinician-teachers and students had low levels of motivation. Competitions for practice diminished learning collaboration. In response to the challenges, adjustments were made to strengthen clinical rotations, engage teaching methods and hire more clinician-teachers.Conclusion The rapid HPE scale-up affected clinical placements, reducing student authentic practice and skill development. There is a need to optimise student enrolment, train clinicians as teachers and improve clinical learning resources. Interprofessional education can optimise student practice. Placement coordination facilitates supervision. Student practice should be expanded to primary healthcare settings.